Analysis of Basic Education Concepts in Ukraine and Canada (in the Field “Advertising and Public Relations”) - Bryukhanova, Halyna (Educational Challenges, 2022)
The aim of the article is to conduct a comparative analysis of basic research concepts in the Ukrainian and Canadian scientific space related to the concepts that characterize the general context of professional training, in particular in the field of advertising and public relations. The research methodology is based on general scientific and terminological methods, the comparative method. As a result, the comparison of the basic research concepts in the Ukrainian and Canadian scientific space are considered, namely, education, professional education, vocational education, continuing education, lifelong learning, competence, profession, trade, professional training, professional competence, advertising education, integral competence of a specialist in advertising and public relations, general competencies of a specialist in advertising and public relations, etc. The results of the research, first of all, can be used in systematization of the accumulated scientific knowledge in the field, synthesis and generalization of scientific achievements of the field, ensuring the successful application of scientific achievements in practice. Conclusions. The comparative analysis of basic research concepts in Ukraine and Canada that characterize the general context of professional training, in particular, in the field of advertising and public relations is done. The experience can be taken into account when reforming education in Ukraine and Canada.